Gender Segregation and Sacred Architecture : A Study of George Street Methodist Church, Peterborough, Ontario - Jarvis, Dale Gilbert (Ethnologies, 1995)
This paper starts with a brief architectural history of George Street United Church, Peterborough, Ontario, which includes an account of a failed attempt at gender segregation which took place in 1889. The paper then looks at Methodist gender construction, masculine and féminine ideals, and its paradoxical notions of “womanhood.” It explores, with examples from contemporary churches, how gender concepts were incorporated into sacred architecture. The article concludes with one explanation for the disintegration of Wesley’s mid-18th-century idea of forced gender ségrégation by the end of the 19th century.